2017
DOI: 10.1097/igc.0000000000001028
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA GAS5, Which Acts as a Tumor Suppressor via microRNA 21, Regulates Cisplatin Resistance Expression in Cervical Cancer

Abstract: ObjectivesThe aims of this study were to investigate the functions of GAS5 as a tumor suppressor in cervical cancer and explore the mechanism.MethodsThe expression of GAS5 and microRNA 21 (miR-21) was detected in primary cervical cancer tissue specimens, as well as in cervical cancer cell lines. We identified the interaction of GAS5 and miR-21 by quantitative polymerase chain reaction, Western blot, and dual-luciferase reporter assay. We also studied the functions of GAS5 in proliferation, apoptosis, migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 44 publications
3
77
2
Order By: Relevance
“…Recently, dysregulation of lncRNAs has been reported to alter many biological processes, including cell cycle, proliferation, apoptosis, invasion, and epigenetic regulation [8-10]. Furthermore, lncRNAs are capable of exerting oncogenic or tumor-suppressive roles, and could be considered as diagnostic or therapeutic targets for patients with cancer [11-14]. Human CRC-specific lncRNA CCAT1-L enhances MYC expression and promotes tumorigenesis in CRC [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, dysregulation of lncRNAs has been reported to alter many biological processes, including cell cycle, proliferation, apoptosis, invasion, and epigenetic regulation [8-10]. Furthermore, lncRNAs are capable of exerting oncogenic or tumor-suppressive roles, and could be considered as diagnostic or therapeutic targets for patients with cancer [11-14]. Human CRC-specific lncRNA CCAT1-L enhances MYC expression and promotes tumorigenesis in CRC [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have shown that lncRNAs and protein‐coding messenger RNAs are interacted by competing for shared miRNAs, that is, the ceRNA hypothesis . For example, GAS5 ncRNA upregulates PTEN by sponging miR‐21 or miR‐222, thereafter inhibiting tumor growth by activating the PTEN/AKT pathway . lncRNA ROR is able to regulate the reprogramming of pluripotent stem cells by modulating stem cell factors OCT4, NANOG, and SRY‐box 2 as a ceRNA .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Liang et al reported that lncRNA LINP1 is upregulated in doxorubicin-and 5-fluorouracil-resistant cells and induced chemoresistance, indicating LINP1 is a potential therapeutic target and may be key to reducing chemoresistance in breast cancer (BC) [30]. Wen et al showed that lncRNA GAS5 could influence cisplatin resistance in cervical cancer (CC) by regulating the phosphorylation of Akt [31]. Xue et al found that lncRNA HOTAIR is upregulated in tamoxifen-resistant BC tissues; its overexpression increased BC cell proliferation and conferred tamoxifen resistance in BC [32].…”
Section: Discussionmentioning
confidence: 99%